Thermal and structural evaluation of composite solar receiver tubes for Gen3 concentrated solar power systems. (April 2022) - Du, Shen; Wang, Zexiao; Shen, Sheng
Abstract: A composite solar receiver tube containing thermally conductive and high-temperature protective layers is proposed to improve its thermal and structural performances. Two combinations of materials, which are Inconel 718/nickel and 316 stainless steel/GRCop-84, are selected based on the similarity in their coefficients of thermal expansion. The solar-to-thermal energy conversion in conjunction with the fluid flow and heat transfer of supercritical carbon dioxide inside the solar tubes is analyzed by computational fluid dynamics. The thermal stress due to different solar tube designs is solved by finite element analysis based on the derived temperature field and pressure distribution. The results show that both maximum thermal stress and maximum temperature in solar tubes could be reduced by the composite design. The maximum thermal stress decreases by 4.1 MPa and 24.0 MPa respectively in Inconel 718/nickel and 316 stainless steel/GRCop-84 composite solar tubes. The performance improvement becomes more significant as the thickness of tube wall and intensity of solar radiation increase. Due to the surface temperature reduction, the entire thermal efficiency of solar tubes could increase by up to 1.3% and the creep issue of high-temperature protective materials can be alleviated. Highlights: Composite solar receiver tube with thermally conductive and protective layers is proposed. Thermal and structural performances of the composite solar receiver tube is characterized. Temperature and stress of solar tubes are efficiently decreased by composite design. Thermal efficiency of solar tube can be improved by up to 1.3% due to low surface temperature.